Data envelopment analysis for Malaysia courier services performance and customer satisfaction / Teoh Yeong Kin, Suzanawati Abu Hasan, and Siti Nur Atikah Zahari - Teoh, Yeong Kin; Abu Hasan, Suzanawati; Zahari, Siti Nur Atikah (UiTM Cawangan Perlis, 2020)
One of the key issues of the current courier services in Malaysia is the efficiency of the courier itself. In today's competition, many factors have recognized that influence the efficiency of courier services. Hence, numbers of analytical models and formulas were introduced to measure the efficiency of courier service. This paper presents a practical approach for identifying the level of customers' satisfaction towards courier service companies using Data Envelopment Analysis and four courier services which were Poslaju, City-Link Express, J&T Express, and GD Express in Hulu Terengganu were selected. Data Envelopment Analysis is chosen in this study because it can deal with complex connections between several inputs and outputs on performance evaluation issues. The input criteria considered in this study are assurance, empathy, reliability, responsiveness, tangibility, and price. Meanwhile, customer satisfaction is chosen as the output criteria. The results showed that Poslaju is ranked as the most efficient company, followed by City-Link Express in second and J&T Express as the third. The least efficiency score obtained makes GD Express as the last ranked courier service among these four courier services. Furthermore, the results are mainly influenced by the input criteria of assurance, empathy, and tangibility. This study helps the customer to select the most efficient courier service that can save their time, money, and energy. Finally, this study also can guide courier services to decide on which criteria are effective to be improved to enhance their business performance.